Pineapple fibre thread as a green and innovative instrument for textile restoration - Kamaruddin, Zumahiran; Mohd Yusof, Nur Farhana (SustaiN Society in Kyoto, Japan, 2016)
Natural fibre is becoming less-frequently used in the current textile industry with the development of new technology whereby the use of synthetic fibre becomes eminent. Since the use of the nature-based thread in the textile restoration has not been thoroughly explored through scientific research, the objective of this study was to determine and analyze the suitability and potentiality of pineapple fibre as instrumental threads in the restoration of batik textile. Two methods of investigation were adopted. First, the traditional making of pineapple leaves as fibre thread was conducted through several stages of material preparation involving extracting and removing the fibre from the surfaces of pineapple leaves. Second, a series of experiment were conducted to analyze and determine the mechanical and physical properties of the thread including acidity level, tensile strength, density and moisture content tests. The study found that this thread has weak acidity and it has useful potential values in tensile strength and extensibility, density and moisture content which make it suitable for textile restoration. Also, it was found based on its compatibility with the batik dye and fabric; the thread has suitable physical properties for the restoration work of the textile. The use of the pineapple fibre thread in the textile restoration is not only safe for the artifact but also is an innovative way of caring for and maintaining the artifact from further damage. Extensive research works on the chemical properties; biotechnology and engineering aspects of the pineapple fibre are required in order to improve the quality and properties of the thread.